2000
DOI: 10.1037/0022-3514.78.3.509
|View full text |Cite
|
Sign up to set email alerts
|

Stress and accessibility of proximity-related thoughts: Exploring the normative and intraindividual components of attachment theory.

Abstract: Three studies examine the effects of stress on the accessibility of proximity-related thoughts. In all the studies, participants reported on their attachment style, and the accessibility of proximity themes and worries in a lexical decision task was assessed upon the priming of a stress or neutral word. In Study 2, the primed stress word was semantically related to attachment themes. In Study 3, lexical decisions were made under low or high cognitive load conditions. Overall, the priming of a stress word led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
240
8
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(284 citation statements)
references
References 52 publications
(93 reference statements)
31
240
8
2
Order By: Relevance
“…Under the condition that a cognitive load exists to tax these resources, suppressed ideation would resurface (Wegner, 1994). Mikulincer, Birnbaum, Woddis, and Nachmias (2000) asked participants to remember a two-digit number (i.e., low cognitive load) or a seven-digit number (i.e., high cognitive load) before identifying the color of words during a Stroop color naming task and found that when the cognitive load was high, the suppressed thoughts were more likely to become accessible. These findings suggest that additional cognitive load could interfere with thought suppression.…”
Section: Concealing Information and Keeping Secretsmentioning
confidence: 99%
“…Under the condition that a cognitive load exists to tax these resources, suppressed ideation would resurface (Wegner, 1994). Mikulincer, Birnbaum, Woddis, and Nachmias (2000) asked participants to remember a two-digit number (i.e., low cognitive load) or a seven-digit number (i.e., high cognitive load) before identifying the color of words during a Stroop color naming task and found that when the cognitive load was high, the suppressed thoughts were more likely to become accessible. These findings suggest that additional cognitive load could interfere with thought suppression.…”
Section: Concealing Information and Keeping Secretsmentioning
confidence: 99%
“…Fear of being single and anxious attachment are theoretically similar in the extent to which individuals experience chronic neediness and insecurity. Both types of insecure individuals may be chronically concerned about attachment figure availability and excessively seek reassurance about an attachment figure's devotion (e.g., Mikulincer et al, 2000;Shaver, Schachner, & Mikulincer, 2005). On the other hand, the key difference between fear of being single and anxious attachment may be the specificity of the attachment figure desired.…”
Section: Discussionmentioning
confidence: 99%
“…Attachment models have been conceptualized with two dimensions that underlie adult attachment styles: avoidant attachment and anxious attachment (Bowlby, 1980). Individuals with a highly avoidant attachment style generally struggle for independence and maintain emotional distance from significant others (Bartholomew, 1990; Mikulincer, Birnbaum, Woddis, & Nachmias, 2000; Mikulincer, Gillath, & Shaver, 2002). Individuals with a highly anxious attachment style are excessively dependent on significant others and worry that persons in close relationships with them will not be available or supportive in stressful times (Fraley & Shaver, 1997; Mikulincer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%